The Effects of Continuous vs. Intermittent Prism Adaptation Protocols for Treating Visuospatial Neglect: A Randomized Controlled Trial - Scheffels, Jannik Florian; Korabova, Sona; Eling, Paul; Kastrup, Andreas; Hildebrandt, Helmut (Frontiers in Neurology, 2021)
Visuospatial neglect may interfere with activities of daily living (ADL). Prism adaptation (PA) is one treatment option and may involve two components: recalibration (more strategic) and realignment (more implicit). We examined whether recalibration or realignment is the driving force in neglect rehabilitation using PA. In a randomized controlled trial with two recruitment series and a cross-over design, 24 neglect patients were allocated to a continuous (PA-c) or intermittent (PA-i) PA procedure. During the PA-c condition, goggles were worn without doffing. In the PA-i condition, patients donned goggles twice (first series of patients) or three times (second series) during training to induce more recalibrations. Primary outcome parameters were performance (omissions) on the Apples Cancellation Test and ADL scores. To assess the efficacy of the PA treatment, we compared effect sizes of the current study with those from three groups from previous studies at the same rehabilitation unit: (1) a passive treatment with a similar intensity, (2) a placebo treatment with a similar intensity, and (3) a PA treatment with fewer therapy sessions. Treatment conditions did not significantly predict scores on primary and most secondary outcome parameters. However, the spontaneous ipsilesional body orientation improved only in patients receiving the PA-i condition and this improvement also appeared in patients showing a strong after-effect (irrespective of condition). Effect sizes for the Apples Cancellation Test and the Functional Independence Measure were larger for both PA treatment protocols than the historical control groups. We conclude that more recalibrations during an intermittent PA treatment may have a beneficial effect on spontaneous body orientation but not on other aspects of neglect or on ADL performance. Clinical Trial Registration: German Clinical Trials Register, identifier: DRKS00018813, DRKS00021539.